2008
DOI: 10.1590/s1415-47572008000100010
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic characterization of Melipona rufiventris Lepeletier 1836 and Melipona mondury Smith 1863 (Hymenoptera, Apidae) by C banding and fluorochromes staining

Abstract: The stingless bees Melipona rufiventris and M. mondury were analyzed cytogenetically by conventional staining with Giemsa, C-banding and sequential staining with the fluorochromes CMA3/DA/DAPI. Both species presented 2n = 18 and n = 9, except for one colony of M. rufiventris, in which some individuals had 2n = 19 due to the presence of a B chromosome. After Giemsa staining and C-banding the chromosomes appeared very condensed and presented a high heterochromatic content, making it difficult to localize the cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 7 publications
2
36
0
1
Order By: Relevance
“…Since the first karyotype described to Melipona (Kerr, 1948) to the present, the chromosome number available for all Melipona species was conservative, all of them presenting 2n = 18 (females) and n = 9 (males) (Rocha et al, 2007). Variations in the number of chromosomes were registered for Melipona quinquefasciata Lepeletier, 1836 (Rocha et al, 2007) and Melipona rufiventris Lepeletier, 1836 (Lopes, 2008), but these variations were attributed to the presence of B chromosomes. Thereby the results observed for M. s. merrillae contrast with the current view that chromosome number is conservative in Melipona (Rocha et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Since the first karyotype described to Melipona (Kerr, 1948) to the present, the chromosome number available for all Melipona species was conservative, all of them presenting 2n = 18 (females) and n = 9 (males) (Rocha et al, 2007). Variations in the number of chromosomes were registered for Melipona quinquefasciata Lepeletier, 1836 (Rocha et al, 2007) and Melipona rufiventris Lepeletier, 1836 (Lopes, 2008), but these variations were attributed to the presence of B chromosomes. Thereby the results observed for M. s. merrillae contrast with the current view that chromosome number is conservative in Melipona (Rocha et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…The genome size of these two Melipona species is also larger than the mean Cytogenetic studies have allowed the division of several Melipona species with the same number of chromosomes (2n = 18) in two groups based on their heterochromatin content. The first group comprises species with low heterochromatin content (M. bicolor, M. quadrisfasciata, M. asilvai, M. marginata and M. subnitida), while species in the second one (M. capixaba, M. compressipes, M. crinita, M. seminigra, M. captiosa, M. scutellaris, M. rufiventris and M. mondury) contain a high heterochromatin content (Rocha and Pompolo, 1998;Rocha et al, 2002;Lopes et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, one mechanism that could give raise to the extra-DNA in M. rufiventris and M. mondury is the higher heterochromatin amount in the chromosomes of these species (Lopes et al, 2008) compared to S. xantotricha (Rocha et al, 2003). Boulesteix et al (2006) have also mentioned that the large heterochromatin amount present in the chromosomes of Drosophila orena may be the main factor responsible for the greater increase in the genome size of this species in comparison to the others species of the Drosophila melanogaster subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…In this species, the number of B chromosomes can range from 0–7 between and within colonies and the size of the B chromosome can also vary among colonies from different geographic locations (Costa et al 1992, Brito et al 1997, 2005, Tosta et al 2004, Martins et al 2014). Likewise, in M.rufiventris a small B chromosome was found in a few individuals (males and females) from one of the six colonies analysed (Lopes et al 2008). Marthe et al (2010) also described the presence of one B chromosome in some individuals of two colonies of P.cupira and Barth et al (2011) observed that colonies of Tetragoniscafiebrigi can harbour individuals with 0, 1 or 2 B chromosomes.…”
Section: Resultsmentioning
confidence: 87%